Management of small bowel polyps: from small to big. Issue 3 (May 2019) - Saurin, Jean Christophe; Benech, Nicolas; Pioche, Mathieu
Abstract : Purpose of review: Benign small bowel polyps or mass are clinically poorly distinguishable from malignant small bowel masses, and the diagnostic conditions are almost the same. The important point for clinicians is first to take advantage of the different available diagnostic tools to optimize the diagnostic algorithm of a small bowel polyp or mass. Next, according to the clinical situation, associated disease or sporadic situation, the difficulty is to adapt the treatment decision to the patient situation. Recent findings: The last 20 years have been marked by the development of major diagnostic tools for small bowel diseases (capsule endoscopy, cross-sectional imaging with enteroclysis and balloon-assisted enteroscopy) and by the major decrease of intra-operative enteroscopy as a diagnostic mean. Summary: On the basis of considerable development of capsule endoscopy and the improvement of cross-sectional small bowel imagining, small bowel polyps represent now a frequent clinical situation for gastroenterologists.